A review found inadequate reporting of case–control studies of risk factors for pancreatic cancer - MacCarthy, A; Dhiman, P; Kirtley, S; Logullo, P; Copsey, B; Collins, GS (Elsevier, 2020)
Objective Case-control studies are often used to identify risk factors for pancreatic cancer. The objective of this study was to evaluate the reporting of case-control studies of the risk factors for pancreatic cancer using the STROBE for case-control studies checklist. Study design and setting We conducted a comprehensive literature search of the MEDLINE and EMBASE databases to identify reports of case-control studies published between 2016 and 2018. We scored article reporting using a reporting adherence form developed from the STROBE checklist for case-control studies, consisting of 14 STROBE items related to the title, abstract, methods, and results sections. Results We included reports of 47 case-control studies investigating a variety of risk factors, such as medical conditions and lifestyle factors. Reporting was inconsistent and inadequate. Efforts to address bias and how the study size was arrived at were particularly poorly described. Study cases were described in more detail than study controls. Conclusion Reporting of case-control studies remains inadequate more than 10 years after the STROBE reporting guideline was published. Our findings suggest that authors do not understand the extent to which study methods and findings should be reported to enable studies to be fully understood and their methods reproduced.